PENDAMPINGAN PENCEGAHAN TINDAK KEKERASAN TERHADAP ANAK DI KOTA BATU PROPINSI JAWA TIMUR - Keppi Sukesi (Universitas Negeri Surabaya, 2020)
The issue of violence against children lately shows increasing symptoms, affecting both girls and boys.Based on this background, the general objective of community service activities is aimed at increasing theawareness and concern of school children, teachers and parents for children's rights and protection againstviolence. Specifically the activities carried out are 1). Socializing children's rights and how to recognizeforms of violence. 2). Providing training and assistance in preventing violence against children. 3). Developmodules, posters to prevent violence against children, and 4). Strengthening School Institutions related tothe prevention of acts of violence against children. The activities were carried out in Batu District and BatuCity Bumiaji District, using training and mentoring methods, to Students, Teachers, Parents, and SchoolCommittees. The results of community service activities responded well by the training participants,consisting of Teachers, Students, Parents of students and school committees. Lecture material anddiscussion were responded by asking a number of questions. Posters are expected to be interesting mediafor students to read and can further increase target knowledge. Posters will be posted on the walls of theschool so that more students are reading, the game media are able to turn on the atmosphere and thecommunity supports this game.